2011
DOI: 10.1063/1.3665221
|View full text |Cite
|
Sign up to set email alerts
|

Stable, biocompatible lipid vesicle generation by solvent extraction-based droplet microfluidics

Abstract: In this paper, we present a microfluidic platform for the continuous generation of stable, monodisperse lipid vesicles 20-110 lm in diameter. Our approach utilizes a microfluidic flow-focusing droplet generation design to control the vesicle size by altering the system's fluid flow rates to generate vesicles with narrow size distribution. Double emulsions are first produced in consecutive flow-focusing channel geometries and lipid membranes are then formed through a controlled solvent extraction process. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 39 publications
(43 reference statements)
5
138
0
Order By: Relevance
“…We evaluated the level of the surface hydrophilicity induced by two commercially available PVA solutions commonly used in PDMS surface modification [27][28][29][32][33][34] . We applied PVA solutions with 87-90% and 99+% hydrolysis degrees on PDMS surfaces that were plasma oxidized under the same conditions (50 W for 1 min) and concluded that the former had a more profound effect on the PDMS surface chemistry both in the short and the long term (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated the level of the surface hydrophilicity induced by two commercially available PVA solutions commonly used in PDMS surface modification [27][28][29][32][33][34] . We applied PVA solutions with 87-90% and 99+% hydrolysis degrees on PDMS surfaces that were plasma oxidized under the same conditions (50 W for 1 min) and concluded that the former had a more profound effect on the PDMS surface chemistry both in the short and the long term (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Our experimental data show that the PVA-treated PDMS surfaces retain their hydrophilicity in the long term. We leveraged PVA solutions with two distinct hydrolysis degrees (87-90% and 99+%) because these are widely used for surface modification in PDMSbased microfluidics 33,34 . Based on a wettability study, we found that PVA with a hydrolysis degree of 87-90% was more efficient in both the short and long term compared with PVA with a 99+% hydrolysis degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the use of F-68 in liposomes can greatly improve the stability of liposomes. 64 More than 80% percent of liposome are present after storage for two days. Consequently, we believe that the presence of F-68 outside the liposomes does not hinder the application of the liposomes, but provides more advantages, such as easier fabrication and better stability.…”
mentioning
confidence: 99%
“…1 A subcategory of microfluidics in which two or more immiscible fluids are introduced to create discrete volumes, these systems have been studied extensively in the past decade to form simple droplets (oil-in-water or water-in-oil), 2,3 double emulsions, 4-7 irregular particles (e.g., Janus particles), 8,9 and lipid vesicles. 10 Continuous emulsion streams are formed in microfluidic systems through specialized geometries-perhaps the most common of which are co-flowing streams, cross-flowing streams, and hydrodynamic flow-focusing 11 -with a primary advantage over conventional methods being precise control of the size and composition of the emulsion.…”
Section: Introductionmentioning
confidence: 99%